Assessing the Relationship Between Leadership Style and Employee Performance in Army Batalion Unit - Zuhaidi, Ismail (2011)
The relationship between leadership style and employee performance should be examined in order to identify which leadership style will increase the employee performance and which leadership style will decrease the employee performance. This is also vital for the management to know what type of leadership style of officers should be assigned with the task of more dealing with personnel because it will dictate the performance of the personnel in regard of the officer who leading them. Therefore, this research was conducted to study the relationship between leadership style and employee performance in order to identify which leadership style relate to employee performance and if there is any relationship, how strong is the relationship between them. This study was conducted at the 5th Battalion Border Regiment, located at Bukit Kayu Hitam, Kedah. Specifically, the objectives were (i) to examine the relationship between transformational leadership style and employee performance and (ii) to examine the relationship between transactional leadership style and employee performance according to the military environment. A total of 165 questionnaires were distributed to 165 officers and lower ranks at the battalion and all the questionnaires were returned for analysis. However, 15 questionnaires were rejected due to their incompleteness; hence only 150 of them were usable for further analysis. Data were analyzed using both descriptive and inferential statistical analysis to interpret data. Findings revealed that both leadership style; transformational leadership style and transactional leadership style were related to employee performance. Both leadership styles were significantly correlated with employee performance where transformational leadership style was the most dominant in predicting the employee performance